Pelatihan Pembuatan Video Pembelajaran sebagai Upaya Peningkatan Kompetensi Digital Guru Bahasa Arab - Abdul Haris Rifai; M.Ainur Roziqi; A. Aghna Rahmawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service activity was motivated by the conventional nature of Arabic language learning in Muhammadiyah schools in Malang. Technological developments have not been optimally utilized, resulting in a less engaging and effective Arabic language learning process. The objective of this activity was to provide an understanding of video-based Arabic language learning materials development techniques and to provide theoretical understanding and practical experience in creating video-based learning materials. This activity took the form of training attended by 21 Arabic language teachers. The results showed an increase in teachers' understanding of video creation and utilization techniques in the learning process. This activity also produced learning video products as output, improved learning quality and practices, and impacted by strengthening teacher professionalism and the quality of Arabic language learning on an ongoing basis.